PERANAN, KEWENANGAN DAN KEDUDUKAN DEWAN KOMISARIS DALAM PERSEROAN TERBATAS - SANGANA TIMOR LUMBAN SIANTAR (PREMISE LAW JURNAL, 2016)
Limited Liability Company is a facility of economic activity in the form of a legal entity. A Limited Liability Company has three organs such as the General Meeting of Shareholders, Board of Directors, and Board of Commissioners. Especially, the function of the Board Commissioners is to oversee the Board of Directors in accordance with the regulation regulated in Law No. 40/2007. A significant amandement found in the new Law No. 40/2007 on Limited Liability Company is about a bigger responsibility of the Board Commissioners that the implementation of the function and role of the Board of Commissioners and their duties in a Limited Liability Company needs to be explained. It is suggested that the authority of Board of Commisioners will implemented well if supported by the harmonious relationship with the parties bound to the Limited Liability Company that the goals of the company can be easily achieved and the interaction between the Board of Commissioners and the Board of Directors in terms of supervision can run well and is not in conflict with Law No. 40/2007. Keywords: Limited Liability Copany, Board of Commisioners, Authority